Wide band interferometryforthicknessmeasurement - Constantino, Santiago; Martínez, Oscar; Torga, Jorge Román (My University, 2003)
In thisworkwepresentthe concept of wide band interferometry as opposed to white-light interferometry to introduce a thickness measurementmethodthatgainsprecisionwhenthebandwidthisreduced to anadequatecompromise in order to avoidthedistortionsarisingfromthe material dispersion. The use of thewidestpossible band is a well established dogma whenthehighestresolutionisdesired in distance measurementswithwhite-light interferometry. Wewill show thatthe dogma fallswhenthicknessmeasurementsmust be carriedoutdue to material dispersion. In factthe precise knowledge of thefrequencydependence of therefractiveindexisessentialforadequatethicknessretrievalfromthe opticalexperiments. Thedevicewepresentisalsouseful to obtainthegroup refractiveindexthatisnecessary to calculatetheabsolutethicknessvalue. As anexample, we show thespreading of a siliconeoilon a reference surface in real time.
Keywords: UTN; Facultad Regional Delta; Wide Band Interferometry; White-light Interferometry; Thicknessmeasurement